Prevalence and correlates of Alzheimer’s disease and related dementias in rural Uganda: cross-sectional, population-based study - Mubangizi, Vincent; Obua, Celestino; Tsai, Alexander C.; Maling, Samuel (BMC Geriatrics, 2020)
Abstract Background: There is a paucity of data on the prevalence and correlates of Alzheimer’s disease and related dementias in sub-Saharan Africa. The aim of the study was to estimate the prevalence and correlates of Alzheimer’s disease and related dementias in rural Uganda. Methods: We conducted a cross-sectional, population-based study in a rural region of southwestern Uganda. The Brief Community Screening Instrument for Dementia was administered to a multi-stage area probability sample of400 people aged 60 years and over. Multivariable logistic regression was used to estimate correlates of probable dementia. Results: Overall, 80 (20%) of the sample screened positive for dementia. On multivariable regression, we estimated the following correlates of probable dementia: age (adjusted odds ratio [AOR], 1.02 per year; 95% confidence interval[CI], 1.10–1.03,p<0.001), having some formal education (AOR, 0.57; 95% CI, 0.41–0.81,p= 0.001), exercise (AOR, 0.44;95% CI, 0.27–0.72,p= 0.001), and having a ventilated kitchen (AOR, 0.43; (95% CI, 0.24–0.77,p=0.001). Conclusions: In this population-based sample of older-age adults in rural Uganda, nearly one-fifth screened positive for dementia.
Keywords: Alzheimer’s disease; Dementia; Sub-Saharan Africa; Uganda